Utility of 3-dimensionally printed models for parent education in pediatric plagiocephaly - Pouya Entezami; Morgan P. Spurgas; Michael W. O'Brien; Lisa C. Newman; Matthew A. Adamo (Elsevier, 2022)
Objectives: Demonstrate the benefits of using 3D printed skull models when counseling families regarding disorders of the cranial vault (namely plagiocephaly and craniosynostosis), as traditional imaging review and discussion is often insufficient. Methods: 3D printed skull models of a patient with plagiocephaly were used during clinic appointments to aid in the counseling of parents. Surveys were distributed following the appointment to evaluate the utility of these models during the discussion. Results: Fifty surveys were distributed (with a 98% response rate). 3D models were both empirically and anecdotally helpful for parents in understanding their child's diagnosis. Conclusion: Advances in 3D printing technology and software have made producing models more accessible. Incorporating physical, disorder-specific models into our discussions has led to improvements in our ability to communicate with our patients and their families. Innovation: Disorders of the cranial can be challenging to describe to the parents and guardians of affected children; using 3D printed models is a useful adjunct in patient-centered discussions. The subject response to the use of these emerging technologies in this setting suggests a major role for 3D models in patient education and counseling for cranial vault disorders.